2014
DOI: 10.5588/ijtld.14.0358
|View full text |Cite
|
Sign up to set email alerts
|

Brief advice to tuberculosis patients in Nepal to stop smoking: a pilot study by the Britain Nepal Medical Trust

Abstract: Brief advice on smoking cessation to patients starting anti-tuberculosis treatment in the National Tuberculosis Programme (NTP) setting in Eastern Nepal led to 39% quitting for least 6 months. Our results should encourage randomised trials in smokers with TB in Nepal: if substantiated, smoking cessation advice should become a mandatory component of the NTP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 15 publications
1
19
0
1
Order By: Relevance
“…Regarding tobacco use disorders, another comorbidity of alcohol use disorders, two smoking intervention studies in Nepal and Pakistan found no reduction of smoking in the control group. 23 , 24 The results from these studies seem to support the idea that routine interventions by health care providers do not prevent tobacco use among TB patients. However, in a large alcohol intervention trial with TB patients in South Africa, daily or almost daily tobacco use significantly reduced over time during TB treatment.…”
Section: Introductionmentioning
confidence: 58%
“…Regarding tobacco use disorders, another comorbidity of alcohol use disorders, two smoking intervention studies in Nepal and Pakistan found no reduction of smoking in the control group. 23 , 24 The results from these studies seem to support the idea that routine interventions by health care providers do not prevent tobacco use among TB patients. However, in a large alcohol intervention trial with TB patients in South Africa, daily or almost daily tobacco use significantly reduced over time during TB treatment.…”
Section: Introductionmentioning
confidence: 58%
“…Campbell et al provided brief advice to TB patients in Nepal [33]. They reported that 39% of the 195 in the intervention group claimed at least 6 months of abstinence, verified by carbon monoxide (CO) measurement in expired air.…”
Section: Smoking Cessation Intervention Is Feasible and Effectivementioning
confidence: 99%
“…Tatsächlich gibt es einige Studien aus Entwicklungsländern mit hoher TB-Prävalenz, die die Auswirkungen der Tabakentwöhnung auf den Verlauf der TB untersucht haben [65]: Ein initiales Motivationsgespräch von 5 -10 Minuten und kurze Erinnerungen bei jeder Visite führten in Indonesien zu einem Anstieg der Nichtraucher nach 6-monatiger Therapie von 86,1 % im Vergleich zu initial 18,5 % Nichtrauchern in 2011 [66]. In Nepal beendeten 39 % einer Kohorte von 77 Rauchern das Rauchen binnen 6 Monaten nach einer kurzen Beratung jeweils zu Behandlungsbeginn, nach 2 und 5 Monaten [67]. In Südafrika führte ein kurzes Motivationsgespräch durch eine Krankenschwester nach 6 Monaten immerhin noch zu einer mindestens doppelt so hohen Rauchabstinenz (21,5 % der 205 neu erkrankten Erwachsenen versus 9,3 % der 204 Kontrollpatienten) [68].…”
Section: Risiko Für Eine Aktive Tb-erkrankungunclassified